Immunohistochemical Detection of PIEZO Ion Channels in the Human Carotid Sinus and Carotid Body - Elda Alba; Yolanda García-Mesa; Ramón Cobo; Patricia Cuendias; José Martín-Cruces; Iván Suazo; Graciela Martínez-Barbero; José A. Vega; Olivia García-Suárez; Teresa Cobo (Biomolecules)
The carotid sinus and the carotid body are major peripheral chemo- and baro(mechano)receptors that sense changes in arterial wall pressure and in oxygen, carbon dioxide, and pH in arterial blood. Recently, it was demonstrated that the PIEZO1 and PIEZO2 mechanoreceptor/mechanotransducers are responsible for the baroreflex in the murine aortic arch (aortic sinus). Furthermore, some experimental evidence suggests that the carotid body could participate in mechanosensing. In this study, we used immunohistochemistry and immunofluorescence in conjunction with laser confocal microscopy to study the distribution of PIEZO1 and PIEZO2 in the human carotid sinus and carotid body as well as in the petrosal ganglion of the glossopharyngeal nerve and the superior cervical sympathetic ganglion. PIEZO1 and PIEZO2 were detected in different morphotypes of sensory nerve formations in the walls of the carotid sinus and carotid artery walls. In the carotid body, PIEZO1 was present in a small population of type I glomus cells and absent in nerves, whereas PIEZO2 was present in both clusters of type I glomus cells and nerves. The most prominent expression of PIEZO1 and PIEZO2 in the carotid body was found in type II glomus cells. On the other hand, in the petrosal ganglion, around 25% of neurons were PIEZO1-positive, and around 85% were PIEZO2-positive; regarding the superior cervical sympathetic ganglion, around 71% and 86% displayed PIEZO1 and PIEZO2, respectively. The results of this study suggest that PIEZO1 and PIEZO2 could be involved in the detection and/or mechanotransduction of the human carotid sinus, whereas the role of the carotid body is more doubtful since PIEZO1 and PIEZO2 were only detected in some nerves and PIEZO2 was present in a small population of type I glomus cells, with PIEZO1 being absent in these cells. However, since immunoreactivity for PIEZO2 was detected in type II glomus cells, researchers should investigate whether these cells play a role in the detection of mechanical stimuli and/or participate in mechanotransduction.